Lepidic growth component as a favorable prognostic factor in non–small cell lung cancer of ≤3 cm. Issue 23 (11th October 2022) - Sato, Daisuke; Matsubara, Hirochika; Matsuoka, Hiroyasu; Kondo, Tetsuo; Sasanuma, Harunobu; Sugimura, Aya; Onuki, Yuichiro; Uchida, Tsuyoshi; Nakajima, Hiroyuki
Abstract: Background: Many non–small cell lung cancer (NSCLC) tumors present complex histology with various components. The effects of the lepidic growth component (LGC) on the prognosis of NSCLC have not been investigated. Here, we investigated whether an LGC is a relevant prognostic factor for NSCLC. Methods: This study retrospectively investigated the clinicopathologic characteristics of 379 patients with NSCLC ≤3 cm who underwent complete surgical resection between 2004 and 2016 at the University of Yamanashi Hospital. The histologic subtypes were classified into NSCLC with or without an LGC. We evaluated the effect of an LGC on the clinicopathologic features and 5‐year overall survival of patients with NSCLC. Results: On final pathology, 214 (56%) of 379 patients had an LGC, and 165 (44%) did not. Sex, smoking history, ground‐glass opacity component, pathologic invasive size, lymph node metastasis, pleural invasion, vessel invasion, pathologic stage, and histologic type were significantly different between the groups. Multivariate analysis of 5‐year overall survival, identified age (hazard ratio [HR], 1.07; 95% confidence interval [CI], 1.035–1.105; p  < 0.001), pathologic invasive size (HR, 1.548; 95% CI, 1.088–2.202; p  = 0.015) and LGC (HR, 2.11; 95% CI, 1.099–4.051; p  = 0.025) as independent prognostic factors. When the pathologic invasive size was matched, the 5‐year overall survival of the LGC and non‐LGC groups was 93% and 77%, respectively ( p  = 0.006). Conclusions: LGC is a significantly favorable prognostic factor for NSCLC with a pathologic invasive size of ≤3 cm. Abstract : Many non–small cell lung cancer (NSCLC) tumors present complex histology with various components. The effects of the lepidic growth component (LGC) on the prognosis of NSCLC have not been investigated. Here, we investigated whether an LGC is a relevant prognostic factor for NSCLC. The histologic subtypes were classified into NSCLC with or without an LGC. The 5‐year overall survival of the LGC and non‐LGC groups was 93% and 77%, respectively ( p  = 0.006). LGC is a significantly favorable prognostic factor for NSCLC with a pathologic invasive size of ≤3 cm.